2007
DOI: 10.1098/rspb.2007.1318
|View full text |Cite
|
Sign up to set email alerts
|

Social diffusion of novel foraging methods in brown capuchin monkeys (Cebus apella)

Abstract: It has been reported that wild capuchin monkeys exhibit several group-specific behavioural traditions. By contrast, experiments have found little evidence for the social learning assumed necessary to support such traditions. The present study used a diffusion chain paradigm to investigate whether a novel foraging task could be observationally learned by capuchins (Cebus apella) and then transmitted along a chain of individuals. We used a two-action paradigm to control for independent learning. Either of two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
100
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 47 publications
8
100
0
5
Order By: Relevance
“…In recent years, majority influence has become a favourable research topic for behavioural biologists. One line of research has focused on our closest living relatives, the nonhuman primates (chimpanzees, Pan troglodytes: Bonnie, Horner, Whiten, & de Waal, 2007;Haun, Rekers, & Tomasello, 2012;Hopper, Schapiro, Lambeth, & Brosnan, 2011;Whiten, Horner, & de Waal, 2005; capuchin monkeys, Cebus apella: Dindo, Thierry, & Whiten, 2008;Dindo, Whiten, & de Waal, 2009;Perry, 2009), which could enable intriguing analysis of the evolutionary roots of this human phenomenon (MacLean et al, 2012). Another line of research has aimed to investigate the possibility of convergent evolution of conformity by focusing on phylogenetically more distant species, such as fish (Day, MacDonald, Brown, Laland, & Reader, 2001;Kendal, Coolen, & Laland, 2004;Pike & Laland, 2010), rats (Galef & Whiskin, 2008;Jolles, de Visser, & van den Bos, 2011;Konopasky & Telegdy, 1977) and fruit flies (Battesti, Moreno, Joly, & Mery, 2012).…”
mentioning
confidence: 99%
“…In recent years, majority influence has become a favourable research topic for behavioural biologists. One line of research has focused on our closest living relatives, the nonhuman primates (chimpanzees, Pan troglodytes: Bonnie, Horner, Whiten, & de Waal, 2007;Haun, Rekers, & Tomasello, 2012;Hopper, Schapiro, Lambeth, & Brosnan, 2011;Whiten, Horner, & de Waal, 2005; capuchin monkeys, Cebus apella: Dindo, Thierry, & Whiten, 2008;Dindo, Whiten, & de Waal, 2009;Perry, 2009), which could enable intriguing analysis of the evolutionary roots of this human phenomenon (MacLean et al, 2012). Another line of research has aimed to investigate the possibility of convergent evolution of conformity by focusing on phylogenetically more distant species, such as fish (Day, MacDonald, Brown, Laland, & Reader, 2001;Kendal, Coolen, & Laland, 2004;Pike & Laland, 2010), rats (Galef & Whiskin, 2008;Jolles, de Visser, & van den Bos, 2011;Konopasky & Telegdy, 1977) and fruit flies (Battesti, Moreno, Joly, & Mery, 2012).…”
mentioning
confidence: 99%
“…Cebus has one of the largest brain sizes relative to body size of any primate [13] and generally excels at cognitive tasks [9]. Therefore, this genus is expected to be good at problem-solving, though opinions regarding the genus' capacity for imitation are mixed [9,[14][15][16]. Capuchins are omnivores specializing in extractive foraging [9,17], so the foraging tasks they routinely need to solve are complex; therefore, it might be expected that they would benefit by having social cues to guide the acquisition of their foraging skills [18].…”
Section: Introductionmentioning
confidence: 99%
“…The realization that there are many forms of social-learning mechanisms and that observations cannot tell them apart (Heyes 1993) caused the development of sophisticated laboratory experiments, where key variables could be controlled by scientists. These laboratory experiments demonstrated that a variety of vertebrate species might be able to learn socially through production imitation (Laland & Plotkin 1990;Bonnie et al 2006;Horner et al 2006;Dindo et al 2008). However, demonstrating that captive animals are able to learn socially in sophisticated ways does not necessarily imply that wild animals of the same species regularly use social learning to solve problems, or that they regularly imitate.…”
mentioning
confidence: 99%